2018
DOI: 10.1159/000486962
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of SH2B1 Variants on Expression of Leptin- and Insulin-Induced Pathways in Murine Hypothalamus

Abstract: Objective: We aimed to determine the effect of human SH2B1 variants on leptin and insulin signaling, major regulators of energy homeostasis, on the RNA level. Methods: We analyzed the expression of infrequent alleles of seven SH2B1 variants (Arg67Cys, Lys150Arg, Thr175Ala, Thr343Met, Thr484Ala, Ser616Pro and Pro689Leu) in response to insulin or leptin cell stimulation. Two of these were identified in own mutation screens, the others were predicted to be deleterious or to serve as controls. The variants were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
(78 reference statements)
1
8
0
Order By: Relevance
“…(3) At the locus 16p.11.2 (see locus 26 in Table 1) higher BMI, BF%, WC, HC, HC adjBMI , and higher risk for obesity were negatively associated with intelligence and educational attainment in line with previous evidence (Jacquemont et al, 2011). Genetic variations [SNPs, copy number variants (CNVs), and larger deletions/insertions] at 16p.11.2 have been shown to be associated with developmental delay, ASD, ADHD, schizophrenia, BD, epilepsy, intracranial volume, brain development, congenital anomalies, altered satiety response, energy imbalance, underweight, and morbid obesity (McCarthy et al, 2009;Bochukova et al, 2010;Fernandez et al, 2010;Walters et al, 2010;Jacquemont et al, 2011;Volckmar et al, 2012;Zufferey et al, 2012;Egger et al, 2014;Qureshi et al, 2014;Volckmar et al, 2015;Maillard et al, 2016;Giuranna et al, 2018;Martin-Brevet et al, 2018;Sonderby et al, 2018;Niarchou et al, 2019). The consequences of 16p11.2 CNV and larger deletions and duplications on health are broad (Crawford et al, 2019;Niarchou et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…(3) At the locus 16p.11.2 (see locus 26 in Table 1) higher BMI, BF%, WC, HC, HC adjBMI , and higher risk for obesity were negatively associated with intelligence and educational attainment in line with previous evidence (Jacquemont et al, 2011). Genetic variations [SNPs, copy number variants (CNVs), and larger deletions/insertions] at 16p.11.2 have been shown to be associated with developmental delay, ASD, ADHD, schizophrenia, BD, epilepsy, intracranial volume, brain development, congenital anomalies, altered satiety response, energy imbalance, underweight, and morbid obesity (McCarthy et al, 2009;Bochukova et al, 2010;Fernandez et al, 2010;Walters et al, 2010;Jacquemont et al, 2011;Volckmar et al, 2012;Zufferey et al, 2012;Egger et al, 2014;Qureshi et al, 2014;Volckmar et al, 2015;Maillard et al, 2016;Giuranna et al, 2018;Martin-Brevet et al, 2018;Sonderby et al, 2018;Niarchou et al, 2019). The consequences of 16p11.2 CNV and larger deletions and duplications on health are broad (Crawford et al, 2019;Niarchou et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…These data provide excellent examples of how to integrate GWAS, eQTL, and ATAC-seq data to identify functional variants at GWAS loci. Further experiments are needed to determine if these variants are the only functional variants at each locus, as we also observed allelic differences in protein binding for a second variant overlapping an ATAC-seq peak at the SH2B1 locus (Figure S5B) and others have suggested different functional variants at this locus,(Giuranna et al 2018; Volckmar et al 2012) and which gene(s) are contributing to obesity risk.…”
Section: Discussionmentioning
confidence: 91%
“…19 A number of genetic studies on humans have suggested that any deficiencies in the insulin-signalling pathway could result from either mutation in the insulin receptor within the SH2B1 gene, or the existence of antibodies against either the insulin receptor or insulin itself, are rarely causing insulin resistance. 20,21 In this study, no effect of population stratification was encountered due to the relative homogeneity of the Jordanian Arab population. This provides useful benefits to genetic studies as smaller numbers of multiple variations occurred in the genes that are responsible for the observed phenotypes, and expected to be identified in populations that are more homogeneous.…”
Section: Discussionmentioning
confidence: 71%